The Role of Islam in the Development of the Arabic Language: History and Its Influence - Ahmad Hidayatullah Zarkasyi; Mohammad Iqbal Gusti Rakasiwi (al-Afkar, Journal For Islamic Studies, 2025)
Arabic was formed long before Islam came or is also called the al-asru al-jahili period. Arabic is part of the South Semitic language family spoken by people living in the Arabian peninsula, in the southwest part of the Asian continent and at the same time by some people it is considered a oldest historical language. As it develops, currently Arabic is the official language in various countries, for example: Qatar, Chad, Palestine, Morocco, Egypt, Lebanon, Libya, Sudan, Oman, Gambia, Somalia, Iraq, Tunisia and many more. There is still a lot of debate about the history of the emergence of the Arabic language, due to the lack of concrete evidence in the form of artifacts etc. that prove the emergence of the Arabic language. This makes it difficult to prove where and when it emerged. The big question is whether Arabic is a derivative of Semitic languages or is it actually its parent. Using the analysis method in this paper, Arabic is found to be very important in the history of Islamic civilization.